The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5194/acp-20-2781-2020
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and size of the particles emitted from a gasoline-direct-injection-engine vehicle and their ageing in an environmental chamber

Abstract: Air pollution is particularly severe in developing megacities, such as Beijing, where vehicles equipped with modern gasoline-direct-injection (GDI) engines are becoming one of major sources of the pollution. This study presents the characteristics of individual particles emitted by a GDI vehicle and their ageing in a smog chamber under the Beijing urban environment, as part of the Atmospheric Pollution & Human Health (APHH) research programme. Using transmission electron microscopy, we identified the particles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…4), implying that ship exhaust-related BC particles were subject to substantial aging during their transport from ocean. It is unexpected that our MACBC,ship(λ) is similar to the value of marine engine emissions (7.8 m 2 g -1 at 780 nm, extrapolated to the same wavelengths of this study by assuming an AAEBC = 1.1) (Corbin et al, 2018), because freshly emitted fossil fuel BC particles tend to be externally-mixed with other substances and become internally-mixed ones after aging (Xing et al, 2020). Actually, the authors of that study also recognize that more work is needed to clarify their ambiguous large MACBC(λ) of marine engine emissions.…”
Section: Source-dependent Optical Properties Of Lac Aerosolsupporting
confidence: 72%
“…4), implying that ship exhaust-related BC particles were subject to substantial aging during their transport from ocean. It is unexpected that our MACBC,ship(λ) is similar to the value of marine engine emissions (7.8 m 2 g -1 at 780 nm, extrapolated to the same wavelengths of this study by assuming an AAEBC = 1.1) (Corbin et al, 2018), because freshly emitted fossil fuel BC particles tend to be externally-mixed with other substances and become internally-mixed ones after aging (Xing et al, 2020). Actually, the authors of that study also recognize that more work is needed to clarify their ambiguous large MACBC(λ) of marine engine emissions.…”
Section: Source-dependent Optical Properties Of Lac Aerosolsupporting
confidence: 72%
“…Even though it is commonly recognized that secondary aerosol mass governs haze formation in megacities in China (Huang et al, 2014;Zhang et al, 2013;Tao et al, 2017;Sun et al, 2018), the contributions of primary (direct) particle sources cannot be neglected. Previous studies have demonstrated that primary emission sources, such as residential heating, traffic and cooking activities, can contribute significantly to both particle number and mass concentrations in the urban atmosphere in China (He et al, 2004a;Xu et al, 2014;Du et al, 2017;Wang et al, 2013;Sun et al, 2018). It was recently reported that traffic could be a major source of nanoclusters (sub-3 nm) in urban environments (Ronkko et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are extensive studies dealing with the health effects of airborne particulate matter (PM) (Rückerl et al, 2011;Brauer et al, 2012;Balakrishnan et al, 2015;Hu et al, 2016;Wang et al, 2017;Li et al, 2020;Xing et al, 2020). Long-term exposure to PM2.5 (i.e.…”
Section: Introductionmentioning
confidence: 99%